2016
DOI: 10.1109/tip.2015.2501755
|View full text |Cite
|
Sign up to set email alerts
|

Robust Face Sketch Style Synthesis

Abstract: Heterogeneous image conversion is a critical issue in many computer vision tasks, among which example-based face sketch style synthesis provides a convenient way to make artistic effects for photos. However, existing face sketch style synthesis methods generate stylistic sketches depending on many photo-sketch pairs. This requirement limits the generalization ability of these methods to produce arbitrarily stylistic sketches. To handle such a drawback, we propose a robust face sketch style synthesis method, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Additionally, they employ Markov networks to model the relationship between neighboring patches. Zhang et al [45] employed a sparse representation-based greedy search strategy to first estimate an initial sketch. Candidate image patches from the initial estimated sketch and the template sketch are then selected using multi-scale features.…”
Section: A Face Photo-sketch Synthesismentioning
confidence: 99%
“…Additionally, they employ Markov networks to model the relationship between neighboring patches. Zhang et al [45] employed a sparse representation-based greedy search strategy to first estimate an initial sketch. Candidate image patches from the initial estimated sketch and the template sketch are then selected using multi-scale features.…”
Section: A Face Photo-sketch Synthesismentioning
confidence: 99%
“…Generating new training sketch data to match more closely to the sketch style of a specific artist of interest (e.g. by using the method proposed by [11]), and training the network with these sketches would overcome this limitation.…”
Section: Fine Artsmentioning
confidence: 99%
“…Few studies developed methods of sketch synthesis to handle more variation in one or more variables at a time, such as lighting [9], and lighting and pose [10]. In a recent study, Zhang et al [11] showed that sketch synthesis by transferring the style of a single sketch could be used also in uncontrolled conditions. In [11], first an initial sketch by a sparse representation-based greedy search strategy was estimated, then candidate patches were selected from a template style sketch and the estimated initial sketch.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…learn a feature dictionary from photo patches and replace these patches with a sparse parametric representation during the searching process. Zhang et al [32] develop a framework to synthesize face sketches trained on only one template sketch use a multi-feature-based optimization model to select candidate image patches. The above approaches can create sketches that closely match an input photo, but it is difficult for their frameworks to generate cartoons in given artistic styles, especially some smooth and fancy styles.…”
Section: Input Portraitmentioning
confidence: 99%